An anthology of graphic fiction, cartoons, & true stories. [Vol. 1] - Brunetti, Ivan (Yale University Press, 2006)
Brunetti offers selections from the works of more than seventy-five avant-garde comic artists. His selections are arranged by genre and grouped thematically--Publisher description.